APPLICATION OF EXTRACTABLE ANTIGEN 1 (EA1) FOR SPECIFIC DETECTION OF BACILLUS ANTHRACIS CELLS - SHIVAKIRAN S MAKAM; JOSEPH J KINGSTON; UPPALAPATI S RAMAKRISHNA; RADHIKA M; URMIL TUTEJA; MURALI H SRIPATHI; HARSH V BATRA (International Journal of Pharma and Bio Sciences, 2013)
Antibody based assays are very important for early and accurate detection of Bacillus anthracis in different sample matrices to initiate effective response and control strategies during biological emergencies and natural outbreaks. To achieve this, murine monoclonal antibodies were generated against Extractable antigen 1 (EA1) of B. anthracis which was proven to be present in abundance in vegetative cells and a persistent contaminant on the spores. EA1 protein was cloned as two regions and expressed in E. coli host to immunize the BALB/c mice and rabbits. Three monoclonal antibodies (EAC105, EAC108 and EAC202) were very promising, as they were highly reactive to recombinant proteins as well as native antigen and also found to be explicitly specific to the pathogen. The monoclonal antibodies were employed in Western blot, dot ELISA and Sandwich ELISA and also tested onto the artificially contaminated meat and blood samples where they were found capable of reacting with the pathogen alone. The present report illustrates application of monoclonal antibodies based on EA1 for developing simple detection systems for B. anthracis.